Recycling of construction materials in Ukraine: legislation, current state, issues, and future prospects for the market of reusing damaged structures - MURASOVA, Olena; GRYGOROVSKYI, Andrii; BRONEVYTSKYI, Andrii (Ways to Improve Construction Efficiency, 2024)
In today’s world, the issue of waste recycling and disposal has reached a large scale. With the continuous development of major cities, construction waste constitutes a significant portion of all waste generated by global economies. Dismantling, recycling, and reusing construction materials is known as recycling, which is a widely recognized concept in developed countries. In Ukraine, where the construction sector was one of the key economic sectors even before the onset of the large-scale aggression by the Russian Federation, the issue of recycling is particularly relevant. Furthermore, since the outbreak of military actions in 2022, the volume of construction waste has significantly increased due to the large number of destroyed buildings and infrastructure facilities. This has led to additional environmental challenges, issues regarding efficient resource use, and the collection and recycling of waste. According to various estimates, up to 30% of all waste is attributed to that generated as a result of military actions. Globally, recycling construction waste is a highly profitable industry. Leading countries have established markets for companies operating in this sector. In most European countries, the level of recycling is quite high. For instance, in the Netherlands, about 90% of construction waste is reused, followed by Belgium at 87%, Denmark at 81%, the United Kingdom at 45%, Finland at 43%, and Austria at 41%. Currently, Ukraine lacks a market for the reuse of construction waste, which negatively impacts the environment and complicates the effective use of secondary materials. The aim of this research is to analyze the existing situation in the recycling sector in Ukraine, taking into account the specific challenges posed by military actions, and to develop recommendations for improving the management system for construction waste. In the context of global challenges related to climate change and sustainable development, the study of recycling construction materials in Ukraine becomes particularly significant. Developing effective technologies and implementing innovative solutions could be a key factor in restoring damaged infrastructure and reducing negative environmental impacts.